Photosensitization of Lipofuscin in Skin Keratinocytes: Effect of Visible Light on Human Skin - Tonolli, Paulo Newton (2018)
Lipofuscin is an autofluorescent pigment progressively accumulated during cellular aging, in several tissues, such as heart, muscle and retina, especially in the postmitotic period. That phenomenon may result from oxidative stress, when biomolecules and organelles (mainly mitochondria) are damaged, generating non-degradable products inside lysosomes. Lipofuscin can be photosensitized, promoting photoxidative processes in cellular components. Many studies on lipofuscin were made using the human retinal pigment epithelial cells, but very little is known about lipofuscin from human skin. In this work we investigated the photoinduced formation (UVA and visible light) of lipofuscin and the consequence of its photosensitization by visible light. We also established an efficient protocol for the induction of lipofuscinogenesis, through specific damage in mitochondria and lysosomes. Cells that accumulated lipofuscin, after exposure to UVA and blue light, became sensitive to visible light (400-750 nm). We characterized the absorption and fluorescence emission of lipofuscin, as well as its fluorescence lifetime through the time resolved fluorescence microscopy (FLIM). We observed that lipofuscin in keratinocytes has absorption maximum in the blue region of light spectrum (420-450 nm), and maximum emission in the red. When photosensitized at 466 nm, lipofuscinloaded HaCaT cells had reduced cell viability, which was related with singlet oxygen generation, accumulated 8-oxo-dG premutagenic lesions and breaks in the DNA strand. Besides, we investigated the efficiency of different wavelengthsin visible light spectrum (408, 466, 522 and 650 nm) to promote lipofuscin formation due to damages in both mitochondria and lysosomes. Blue (408 and 466 nm) and green light (522 nm), but not red light (650 nm), promoted damage in mitochondria (membrane and DNA integrity) and lysosomes (membrane integrity and autophagic activity), effectively inducing lipofuscinogenesis. Thus, in addition to UVA, visible spectrum itself increases the sensitivity of keratinocytes to the visible light, through the generation of lipofuscin. Finally, we tested the carcinogenic potential of high-energy blue light (408 nm), by chronically irradiating HaCaT cells. For the first time in the literature, the formation of pyrimidine cyclobutane (CPD) dimers in the nuclear DNA of HaCaT cells was observed immediately or after several cycles of irradiation at 408 nm. We identified four major changes involved with the process of malignant transformation: genomic instability, decrease in the expression of tumor suppressor protein p16INK4a, increase in the proliferation rate and resistance to UVA-induced apoptosis